Property rights and wrongs: Land reforms for sustainable food production in rural Mali - Totin, Edmond; Segnon, Alcade C; Roncoli, Carla; Thompson-Hall, Mary; Sidibé, Amadou; Carr, Edward R. (Elsevier, 2021)
Agricultural land reforms are crucial to promote investments in sustainable land management and food production amidst accelerating urbanization and increasing population growth. However, notable gaps remain in the literature regarding how land reforms designed at the national level are implemented in localized contexts, especially as they interplay with customary tenure regimes. Adopting an institutional bricolage perspective, we explore interactions between local tenure arrangements and government land reforms and the resulting implications for food production in rural Mali. We show that specific market-based land tenure arrangements in the study area emerged from a combination of urbanization pressures and government-designed land reform. We find that tenure security is linked to agricultural investment decisions, as also documented by previous studies. We likewise show that anxieties and ambiguities stemming from state-mandated land registration foster the emergence of monetized forms of access to collective land. These new market-based systems drive greater out- migration of productive community members, leading to labour shortages and weakening the social cohesion and mutual support systems upon which the most vulnerable depend. The findings show that top-down land reforms in rural Mali lead to disruptions of the social fabric, along with re-organizations of tenure systems to accommodate social norms and priorities. We illustrate how, in the context of centralized policy making with limited local consultation, community members resist cooperating and creatively search for alternatives to achieve their social goals. Empirical investigations of socio-institutional challenges such as land tenure arrangements are critical for effective scaling of agricultural innovations and sustainable food production.